When contaminated dietary supplements cause positive drug tests: methylhexaneamine as a doping agent in sport - Denham, B. E. (International Journal of Sport Policy and Politics, 2017)
Researchers estimate that contaminated dietary supplements cause between 6.4% and 8.8% of all positive drug tests in competitive sport. Methylhexaneamine (DMAA), an amphetamine derivative banned by the World Anti-Doping Agency (WADA) in 2009, has caused more positive tests than any other stimulant. The current article examines DMAA as a potentially hazardous supplement contaminant and doping agent, beginning with an historical overview. Sections addressing its status as both a performance-enhancing substance and potential health threat follow. The article then situates methylhexaneamine in a sport-policy context, identifying DMAA-related challenges to the effective and uniform enforcement of the WADA Code. A final section offers suggestions for both athletes and athletic organisations.